2018
DOI: 10.1007/s00775-018-1605-1
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the human glutaminyl cyclase–SEN177 complex indicates routes for developing new potent inhibitors as possible agents for the treatment of neurological disorders

Abstract: Recent evidence links the role of human glutaminyl cyclase (hQC) to the amyloidogenic process involved in Alzheimer's disease (AD). hQC is a zinc enzyme present in neuronal tissue and its activity is responsible for the cyclization of N-terminal Gln or Glu β-amyloid peptides, leading to N-pyroglutamic acid peptides (pE-Aβ) that is probably a crucial event in the initiation and progress of the disease. Indeed, pE-containing peptides exhibit an elevated neurotoxicity and a tendency to aggregate. These observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In addition to validating the impact of the glutaminyl cyclase inhibitor first reported by Logtenberg et al, we determined the IC50 of SEN177 inhibition of SIRPα binding to be 280 nM. This indicates a lower potency than the IC50 reported for inhibition of glutaminyl cyclase activity in a biochemical assay (20 nM [46]), but is consistent with the efficacy of the concentration (10 μM) employed in cells by Logtenberg et al…”
Section: Lsc Assay Confirmed That Cd47 Post-translational Modificatiosupporting
confidence: 84%
“…In addition to validating the impact of the glutaminyl cyclase inhibitor first reported by Logtenberg et al, we determined the IC50 of SEN177 inhibition of SIRPα binding to be 280 nM. This indicates a lower potency than the IC50 reported for inhibition of glutaminyl cyclase activity in a biochemical assay (20 nM [46]), but is consistent with the efficacy of the concentration (10 μM) employed in cells by Logtenberg et al…”
Section: Lsc Assay Confirmed That Cd47 Post-translational Modificatiosupporting
confidence: 84%
“…Crystallographic studies have shown that an N‐terminal pyro‐glutamate in CD47 is located at the binding site for its ligand SIRPα (CD172α) 14 . The formation of this pyro‐glutamate is catalyzed by the enzyme QC, 46 which can be inhibited by small molecules such as SEN177 18 . A genetic screen has demonstrated the impact of QPCTL for the binding affinity of CD47 to SIRPα and its functional relevance for tumor cell killing 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of QPCTL to the affinity of CD47 for SIRPα binding, and that this interaction is “druggable” by QPCT/QPCTL inhibitors, has recently been established by two independent studies 16,17 . A prototypic QPCT/QPCTL inhibitor is the small molecule SEN177, which contains a triazine ring as the QC binding motif 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different CD47 antibody (B6H12), we confirmed that overall CD47 protein expression and cell surface localization were not decreased upon transduction with sgRNAs targeting QPCTL (Figures 2D, E; Figure S4). We then tested two small molecule inhibitors of QPCTL, SEN177 29 and PQ912 [30][31][32] , to validate that the enzymatic activity of QPCTL is required for the observed loss of CC2C6 binding, but not B6H12 binding (Figures 2D, F, G;…”
mentioning
confidence: 99%